Pengaruh Augmented Reality Marketing, Online Customer Review, Persepsi Harga terhadap Purchase Decision dan Repurchase Intention (Studi pada Konsumen Maybelline Official Store di Shopee) - Hapshoh, Nabilah Adawiyah Al; Wusko, Any Urwatul (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study was conducted to determine the effect of Augmented Reality Marketing, Online Customer Review, Price Perception on Purchase Decision and Repurchase Intention (Study on Maybelline Official Store Consumers at Shopee)". This type of research uses explanatory research with a quantitative approach, with the distribution of questionnaires as a data collection technique. The sampling method uses purposive sampling technique, which is a sampling technique where the person selected as the sample is in accordance with the purpose of the research, the sample used was 116 respondents through distributing questionnaires. The data analysis and processing method used in this research is SEM-PLS analysis using Smart PLS 4.0 software. The results of this study show that (1) Augmented Reality Marketing has a positive and insignificant effect on the Purchase Decision of Maybelline Official Store Consumers on Shopee, (2) Online Customer Review has a positive and significant effect on the Purchase Decision of Maybelline Official Store Consumers on Shopee, (3) Price Perception has a positive and significant effect on Purchase Decision Maybelline Official Store Consumers on Shopee, (4) Augmented Reality Marketing has a positive and insignificant effect on Maybelline Official Store Consumer Repurchase Intention on Shopee, (5) Online Customer Review has a negative and insignificant effect on Maybelline Official Store Consumer Repurchase Intention on Shopee, (6) Price Perception has a positive and significant effect on Maybelline Official Store Consumer Repurchase Intention on Shopee, (7) Purchase Decision has a positive and significant effect on Maybelline Official Store Consumer Repurchase Intention on Shopee.